Development of an electrochemical immunosensor for fumonisins detection in foods - Kadir, Mohamad Kamal Abdul; Tothill, Ibtisam E. (MDPI, 2010)
An electrochemical affinity sensor for the determination of fumonisins mycotoxins (Fms) using monoclonal antibody modified screen-printed gold electrode with carbon counter and silver-silver chloride pseudo-reference electrode is reported in this work. A direct competitive enzyme-linked immunosorbent assay (ELISA) was initially developed, exhibiting a detection limit of 100 µg·L-1for fumonisins. This was then transferred to the surface of a bare gold screen-printed electrode (SPGE) and detection was performed by chronoamperometry, monitoring the reaction of 3,3',5,5'-Tetramethylbenzidine dihydrochloride (TMB) and hydrogen peroxide (H2O2) catalysed by HRP at -100 mV potential vs. onboard Ag-AgCl pseudo-reference electrode. The immunosensor exhibited detection limit of 5 µg·L-1 fumonisins with a dynamic range from 1 µg·L-1-1000 µg·L-1. The sensor also performed well in extracted corn